The description on the effects of alcoholism in relation to the university students’ academic progression - Michael B. Welwel; Niyitegeka Josue; Baraka T. Adolph Mushobozi; Alvin A. Kessy; Frank R. Mkwama; Abel J. Mtweve; Joshua Juma Mugane (Universitas Airlangga, 2022)
This study was done so as to determine how the effects of alcoholism among university students can affect their academic progression. Survey Research Design was employed during data collection, within a sample of 300 respondents, who were obtained through purposive sampling technique. Questionnaires were distributed to 290 students because they live with/among the addicted students; while interviews were also done to 10 students and lecturers because they have clear details concerning the addicted student, who have encountered hindrances on academic matters due to alcoholism. The obtained data are presented in tables, showing frequencies and percentages of each item, while others are explained as theories, concepts and views. For those cases, alcoholism among university students has been proven to be accompanied with unsafe sexual practices, which results into unwanted pregnancies and STDs like gonorrhea, syphilis, UTI, HIV/AIDS, etc. Due to alcoholism, most of students have been involved in accidents and injuries, which make them ill and not attend lectures. Some have developed kinds of aggressive behaviors that makes them indiscipline and violent. Such factors hinder their academic prosperity due to failing in exams, attaining low GPAs, prosponding the semester(s) due to financial crisis after squandering school fees, and being incompetent within their profession. Then if so, universities should set strategies and techniques in order to educate the fresh year students who have not been addicted. Rehabilitation counselling should take part to eliminate alcohol dependency on their students. And lecturers should use professional skills to ensure all students attend lectures.